Loving in the war years: And other writings, 1978-1999 - Moraga, Cherrie (Haymarket Books, 2023)
Une édition mise à jour combinant deux œuvres classiques de la littérature chicana et queer, avec une nouvelle introduction de l'écrivaine et sommité renommée Cherríe Moraga. Pour célébrer le 40e anniversaire de sa publication originale, cette édition mise à jour de Loving in the War Years combine les mémoires classiques de Moraga avec La dernière génération : poésie et prose, qui constitue une pierre de touche stimulante, inspirante et perspicace pour les artistes et les activistes, ainsi que pour toustes cielles qui s'efforcent de favoriser l'accueil et la communauté. Les puissants mémoires de Cherríe Moraga restent plus urgents que jamais. Elle explore les intersections de ses identités chicana et lesbienne, se déplaçant avec grâce entre poésie et prose, espagnol et anglais, récits personnels et théorie politique. Moraga raconte avoir parcouru le monde en grande partie en tant qu'étrangère, encerclant les sociétés interconnectées qui l'entouraient dans une perspective lointaine mais observatrice. En fin de compte, cependant, ses écrits servent de pont entre ses cultures, ses langues, sa famille et elle-même, lui permettant de regarder à l'intérieur pour forger des liens à partir de parties autrement inaccessibles de son monde intérieur, pour montrer à quel point la profonde conscience de soi et l'engagement compatissant envers son propre l'environnement est essentiel à la construction d'une solidarité mondiale entre les peuples et les mouvements politiques.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; chicanas; histoire et politique; lesbianisme; mémoire collective; personnes lesbiennes; poésie; périodes historiques; queer; thématiques

Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

Fear of a queer planet queer politics and social theory - Warner, Michael; Social Text Collective (University of Minnesota Press, 2007)
In recent years, lesbians and gay men have developed a new, aggressive style of politics. At the same time, innovative intellectual energies have made queer theory an explosive field of study. In "Fear of a Queer Planet", Michael Warner draws on emerging new queer politics, and shows how queer activists have come to challenge basic assumptions about the social and political world. Existing traditions of theory - Marxism, cultural studies, psychoanalysis, anthropology, legal theory, nationalism, and antinationalism - have too often presupposed a heterosexual society, as the essays in this volume demonstrate. "Fear of a Queer Planet" suggests a new agenda for social theory. It moves beyond the idea that lesbians and gay men share a minority identity and special interests and that their issues can be subordinated to more general social conflicts. Instead, Warner and the other contributors to this volume show that queer sexualities take many forms, are the subject of many kinds of conflict and struggles, and must be taken as a starting point in thinking about cultural politics. This collection explores the impact of ACT UP, Queer Nation, multiculturalism, the new religious right, outing, queerness, postmodernism, and other shifts in the politics of sexuality. The authors featured speak from different backgrounds of gender, race, nationality, and discipline. Together, they show how struggles over sexuality have profound implications for progressive politics, social theory, and cultural studies. Michael Warner has written extensively on censorship and the public sphere, the construction of American literary history, and the social and political implication of literary theories. He is author of "The Letter of the Republic: Publication and the Public Sphere in Eighteenth-Century America" and co-editor of "The Origins of Literary Studies in America: A Documentary Anthology".
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; histoire et politique; militance; premier cycle; périodes historiques; queer; science politique et droit; sciences politiques; soc2014; thématiques; théories sociales

La réflexion queer : apports et limites - Lamoureux, Diane (Dialogues sur la troisième vague féministe, 2005)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Mariage gai: les coulisses d'une révolution sociale - Larocque, Sylvain (Flammarion, 2005)
Certains l’ont vu comme le plus important débat social de notre époque, c’est en tout cas une question déchirante, sur laquelle ont dû se pencher la plupart des pays occidentaux. Ce livre raconte l’histoire inédite du mariage gai au Canada : la bataille des arguments juridiques et politiques, les stratégies secrètes et surtout les jeux de coulisses qui ont conduit à cette nouvelle avancée des droits de la personne.Pour témoigner des motivations des couples qui ont amorcé le mouvement, puis des juges et des politiciens qui ont pris le relais, Sylvain Larocque s’appuie sur une trentaine d’entrevues exclusives, y compris avec le premier ministre Paul Martin, des ministres, des conseillers politiques et des avocats. On saisit ce qui a convaincu Jean Chrétien et son successeur d’aller de l’avant avec cette véritable « patate chaude » ; on comprend ce qu’ont ressenti les opposants face à cette redéfinition d’une institution millénaire ; on mesure l’ampleur d’une controverse qui en appelait aux convictions intimes de chacun. Suivant Sylvain Larocque Sylvain Larocque est correspondant parlementaire de La Presse Canadienne à Ottawa. Il a suivi de près les tractations juridico-politiques ayant entouré le mariage homosexuel.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; mariage; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Aimez-vous le queer? - Schehr, Lawrence R. (Cahiers de recherches des instituts néerlandais de langue et de littérature française, 2005)
Lawrence Schehr's introduction to this collection of essays covers key landmarks in twentieth-century representations of homosexuality in French literature and culture. Beginning with Gide's and Proust's classical and aristocratic representations of homosexuality, subdued within discourses of power and language consonant with the turn of the century, Schehr proceeds to identify the literary and cinematic innovations of Cocteau and Genet as united in their respective revolt against the totalizing structures and discourses of their illustrious predecessors. After discussing the Second World War, the consumerism of the 1960s, and the emerging ‘culture gay’, Schehr fast-forwards to the advent of the paradox of queer theory in the 1990s, highlighting its theoretical (mis)appropriations, from the positive critique of heteronormativity to its insignificance ‘pour le séropositif mourant dans un lit d'hôpital’ (p. 10), acknowledging along the way that queer theory is both ‘made in the USA’ (p. 11) and subject to that continent's imperializing tendencies and ancillary oversights. The editor promises queer readings of French literature and film, but then proffers post-queer readings. Many of the contributions are stimulating and rich in insights. Owen Heathcote's study of the military uniform as both mask and precursor of the collapse of masculinity in novels by Balzac and the cinema of Claire Denis earmarks the uniform as the queerizing stuff of maleness. James Williams's exploration of Jean Cocteau's influence on the cinema of Jean-Luc Godard also unearths a queerization at the heart of Godard's aesthetic creation. In a fascinating contribution, Elizabeth Stephens deconstructs the ‘wall’ of repression and solitude (and its associations with closeted representations of homosexuality) in order to expose the ‘fissures dans les murs genetiens’ (p. 133), demonstrating how Genet subverts categories of heteronormative language in the pursuit of repressed homoerotic desire. Drew Jones conducts a thoroughly lucid exegesis of the distinction between sexual desire (act) and homosexual ‘identity’ in Genet's Querelle de Brest. Countering the Sartrean notion that Genet's treatment of homosexuality (as value in crime and disgust against authority) is not existential (‘homosexuel en soi’ but not ‘pour soi’), Jones argues that Querelle breaks free of essentialist homosexuality by resisting the naming and categorizing hegemony of an Identity as ‘pederast’ that society has conferred on him. It would have been a treat to see how this collection would have evolved had the ‘projet scientifique’ first envisaged been followed through; this ‘projet’ clearly reflected the earlier symmetry of Schehr's tripartite schematization of homosexual cultural production from Proust to queer, but I suspect would have given the collection a different direction. The articles are the collection's real focus, and their value for students and academics with interests in gay and lesbian cultural production in France is unquestionable.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

L'invention de l'hétérosexualité - Katz, Jonathan (Grands classiques de l'érotologie moderne, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis